EVALUASI PROGRAM ROAD SAFETY PARTNERSHIP ACTION POLICE GOES TO SCHOOL DI SMA NEGERI 6 DAN SMK PEMBANGUNAN KOTA BOGOR - Wulandari, Retno; Salbiah, Euis; seran, M.YGG (JURNAL GOVERNANSI, 2017)
The purpose of this study Â is to know the Road Safety Partnership Action Program Police Goes To School at SMAN 6 and SMK Pembangunan in Bogor City.The theory used in this research is by using policy evaluation from William N. Dunn which stating that to measure the success of an evaluation of the program can be measured through six variables: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The method used is descriptive analysis using quantitative approach. Data analysis technique used is by using the calculation of Weight Mean Score (WMS). Data collection techniques used are literature studies and field studies. The study population are 1,857 students from two schools. While the sampling technique used is proportionate stratified random sampling (stratified proportional). The samples using Yamane formula thus obtained sample are 180 respondents.The results of Program Evaluation Research Road Safety Partnership Action Police Goes To School in SMA 6 and SMK Pembangunan Bogor City obtained a score of 3.64 (in scale of 5) which, according to the interpretation of the criteria that are in âgoodâ categories, although it is still the number of violations that occurred among students. This happens due to the lack of awareness of students in traffic, do not care about the safety and ignore the socialization conducted by the police about the ethics of a good drive to support traffic safety and reduce the number of traffic violations or accidents. Efforts are being made to address the problem is by imposing preventive methods (prevention) and applying repressive methods (in applying force). Keywords: Evaluation, Program, Violation